A checklist of the centipedes (Chilopoda) of Lithuania - Tuf, Ivan Hadrián; Ivinskis, Povilas; Rimšaitė, Jolanta (Zootaxa, 2015)
Only 4 species of centipedes were previously reported for Lithuania. Here we present current distributional data for a total of 20 species (12 species of Lithobiomorpha and 8 species of Geophilomorpha) collected mainly during 7 years conducting ecological research at Curonian Spit, drawing on samples from the central, eastern and north-western parts of Lithuania.